Ekspresi New York Esophageal Squamous Cell Carcinoma-1 (NYESO-1) pada Sarkoma Sinovial dan Non Sarkoma Sinovial Lainnya Sebagai Dasar Pemilihan Pemberian Imunoterapi - Ros Nirmawati,; Siregar, Nurjati Chairani; Evelina Kodrat (Majalah Patologi Indonesia, 2021)
BackgroundSynovial sarcoma is a rare high grade soft tissue sarcoma. Nowdays, the available therapeutic modalities has not given asatisfactory result yet. Currently, there is a promising therapeutic strategy through immunotherapy targeting NY-ESO-1 which isexpressed on tumor. The aim of this study was comparing NY-ESO-1 immunoexpression between synovial sarcoma and itshistologic mimics i.e. malignant peripheral nerve sheath tumor (MPNST) and dermatofibrosarcoma protuberans (DFSP)MethodsA cross sectional study was done in 28 cases of synovial sarcoma, 10 cases of MPNST and 17 cases of DFSP from archievalmaterial in Department Anatomical Pathology, FMUI/RSCM from January 2013 to June 2019. Immunohistohemical stainning wasperformed using an antibody NY-ESO-1 and it was described positive if it was expressed in more than 50% of tumor with moderateto strong positive intensity.ResultsThere is a significant difference (p<0.001) in NY-ESO-1 immunoexpression among synovial sarcoma (18/28), MPNST (2/10) andDFSP (1/17). Furthermore, synovial sarcoma showed a significantly higher immunoexpression compared to MPNST (OR 7.2;p=0.016; power 68.7%) and DFSP (OR 28.8; p<0.001; power 98.9%).ConclusionSynovial sarcoma showed a higher expression of NY-ESO-1 thus makes it as a good candidates for immunotherapy. There aredifferences in the expression of NY-ESO-1 in synovial sarcoma against MPNST and DFSP.